European Photography Award 1985-1994 : Deutsche Leasing's Support for the Arts. - Ammann, Jean-Christophe; Müller-Pohle, Andreas; Figge, Horst; von Amelunxen, Hubertus; Kulturzentrum Englische Kirche Galerie Scheffel, Bad Homburg v.d. Höhe (Ostfildern : Cantz Verlag, 1994)
Bergling, Angela ; Braeckman, Dirk ; Buyle-Bodin, Gilles ; Charles, Hervé ; Collins, Hannah ; Cox, Marina ; van Dinther, Lenni ; Duncker, Henrik ; Tuunanen, Yrjö ; Eiussfeldt, Dörte ; Ennadre, Touhami ; Florschuetz, Thomas ; Fox, Anna ; et al.
Published on the occasion of the exhibition 'European Photography Award 1985-1994', Kulturzentrum Englische Kirche, Bad Homburg v.d. Höhe
kunstcatalogus